A framework for studying risk factors for lower extremity musculoskeletal discomfort in nurses. Issue 12 (1st December 2020) - Li, Jing; Sommerich, Carolyn M.; Chipps, Esther; Lavender, Steven A.; Stasny, Elizabeth A.
Abstract: Lower extremity musculoskeletal discomfort (MSD) is prevalent, but understudied, in nurses. A comprehensive, theoretical, aetiological model of lower extremity work-related MSD in hospital in-patient staff nurses was developed through a review of the literature to provide a framework for aetiological and intervention research. The framework informed the design of a survey of 502 hospital staff nurses. Symptom prevalence ranged from 32% in hip/thigh to 59% in ankle/foot regions. Logistic regression modelling using survey data showed that different work and personal factors were associated with discomfort in different regions of the lower extremity. Individual factors (e.g. older age, higher BMI or having any foot condition), physical factors (e.g. higher frequency of patient handling), psychosocial factors (e.g. lower job satisfaction) were associated with discomfort in one or more parts of the lower extremity. Future research should target these factors for intervention, to attempt to reduce occurrence of lower extremity discomfort in nurses. Practitioner Summary: Practitioners may find useful the illustrated, theoretical aetiological model of factors that could influence the prevalence of lower extremity discomfort in nurses. The model could guide conversations with nurses and observational analyses of nursing work. The model and survey results may provide ideas for intervention exploration. Abbreviations: MSD: musculoskeletal discomfort; BMI: body mass index; MSK: musculoskeletal; ICU: intensive care unit; NLERF: nurses' lower extremity MSD risk factor; NASA-TLX: NASA-task load index